2019
DOI: 10.1016/j.cognition.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor contingency modulates breakthrough of virtual 3D objects during a breaking continuous flash suppression paradigm

Abstract: To investigate how embodied sensorimotor interactions shape subjective visual experience, we developed a novel combination of Virtual Reality (VR) and Augmented Reality (AR) within an adapted breaking continuous flash suppression (bCFS) paradigm. In a first experiment, participants manipulated novel virtual 3D objects, viewed through a head-mounted display, using three interlocking cogs. This setup allowed us to manipulate the sensorimotor contingencies governing interactions with virtual objects, while charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…These results seem to be at odds with Bayesian accounts of perception, but are in line with most previous reports regarding the influence of action on visual awareness [23,26,27,31] . According to Bayesian models of perception, the brain uses probabilistic information to optimise inferences about the state of the environment [38,39,60] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results seem to be at odds with Bayesian accounts of perception, but are in line with most previous reports regarding the influence of action on visual awareness [23,26,27,31] . According to Bayesian models of perception, the brain uses probabilistic information to optimise inferences about the state of the environment [38,39,60] .…”
Section: Discussionsupporting
confidence: 90%
“…It was found that these movements lasted longer (i.e., the sphere was visible for a longer period of time) when the direction and speed of rotation were controlled by hand movements than when the subject had no motor control over the stimulus. However, more recent studies -using both binocular onset rivalry [23] and continuous flash suppression paradigms [26,27] -did not find increased access to awareness of stimuli whose rotation is congruent with manual actions. It is possible that these discrepancies are partly due to the use of different methods for presenting stimuli.…”
Section: Introductionmentioning
confidence: 85%
“…Nor do our learned associations correspond to temporally extended relationships between actions and sensory signals, such as when an object is rotated (e.g. Suzuki et al, 2019). As such, the sensorimotor predictions used here do not correspond to fully-fledged sensorimotor contingencies, but rather to simpler sensorimotor mappings.…”
Section: Discussionmentioning
confidence: 86%
“…Voluntary action has been found to help disambiguate a bistable or otherwise ambiguous percept if the action is congruent with an aspect of that percept, e.g. when the direction of movement corresponds to the direction of moving dots (Beets et al, 2010;Di Pace & Saracini, 2014;Maruya, Yang, & Blake, 2007;Mitsumatsu, 2009;Suzuki, Schwartzman, Augusto, & Seth, 2019). A comparable effect has been found for proprioception, where correspondence between the target and proprioceptive information can bias or sharpen the visual percept (Butz, Thomaschke, Linhardt, & Herbort, 2010;Salomon, Lim, Herbelin, Hesselmann, & Blanke, 2013;Yon, Gilbert, De Lange, & Press, 2018).…”
Section: Introductionmentioning
confidence: 90%
“…Until now, it could not have been tested, as the available methods so far did not allow researchers to even probe pre-conscious processing of 3D items. Current methods are all based on screen-presented psychophysical manipulations, and are therefore limited to 2D, on-screen stimuli (for review, see Breitmeyer, 2015), or, recently, to virtual objects (Suzuki et al, 2019). Here, we use a novel variant of the Continuous Flash Suppression paradigm (CFS; Tsuchiya & Koch, 2005) we developed, termed "Real-life" CFS (Korisky et al, 2018) to uniquely suppress real, 3D objects.…”
Section: Introductionmentioning
confidence: 99%